Management of Oblique Root Fracture Using Mineral Trioxide Aggregate: A Case Report - Le Phuong, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4DO - 10.25073/2588-1132/vnumps.4342, 2021)
Root fractures are relatively uncommon compared to other types of dental traumas. It is sometimes extremely difficult for practitioners to decide what should be done and which approach was the optimal choice for patients. This study describes the treatment of an oblique root fracture in the right maxillary central incisor (tooth 11) using mineral trioxide aggregate (MTA) and lingual splint with composite and 0.3 mm 3-strand twisted stainless steel wire. The study performs a detailed management from the first visit to the next appointments. After four months, the tooth was asymptomatic with neither discoloration nor draining sinus. Radiographs show the increasing of periapical radiolucency in the fracture area. Thus, the tooth needs further interventions. Keywords: Dental trauma, root fracture, mineral trioxide aggregate, dental trauma splint. References [1] J. O. Andreasen, L. Andreasen, F. M. Andreasen, R. Fractures, F. M. Andreasen, J. O. Andreasen, G. Tsilingaridis, Textbook and Color Atlas of Traumatic Injuties to the Teeth, John Wiley & Sons Ltd Edition, UK, 2019, pp. 377-407. [2] M. Gharechahi, Horizontal Root Fracture Accompanied by Luxation of Coronal Fragment in a Maxillary Central Incisor: a Case Report, Journal of Dental Research, Dental Clinics, Dental Prospects, Vol. 7, No. 4, 2013, pp. 244-247, https://doi.org/10.5681/joddd.2013.039. [3] M. M. Bornstein, A. B. W. Hanssen, P. Sendi, T. Von Arx, Comparison of Intraoral Radiography and Limited Cone Beam Computed Tomography for the Assessment of Root-Fractured Permanent Teeth, Dental Traumatology, Vol. 25, No. 6, 2009, pp. 571-577, https://doi.org/10.1111/j.1600-9657.2009.00833.x. [4] J. J. May, N. Cohenca, O. A. Peters, Contemporary Management of Horizontal Root Fractures to the Permanent Dentition: Diagnosis-Radiologic Assessment to Include Cone-beam Computed Tomography, Journal of. Endodontics., Vol. 39, No. 3, 2013, pp. S20-S25, https://doi.org/ 10.1016/j.joen.2012.10.022. [5] P. Makowiecki, A. Witek, J. Pol, J. B. Radlińska, The Maintenance of Pulp Health 17 Years After Root Fracture in a Maxillary Incisor Illustrating the Diagnostic Benefits of Cone Beam Computed Tomography, International Endodontic Journal, Vol. 47, No. 9, 2014, pp. 889-895, https://doi.org/10.1111/iej.12221. [6] C. Bourguignon, International Association of Dental Traumatology Guidelines for the Management of Traumatic Dental Injuries: 1. Fractures and Luxations, Dental Traumatology, Vol. 36, No. 4, 2020, pp. 314-330, https://doi.org/10.1111/edt.12578. [7] American Association of Endodontists, , The Recommended Guidelines of American Association of Endodontists for the Treatment of Traumatic Dental Injuries, https://www.aae.org/specialty/clinical-resources/treatment-planning/traumatic-dental-injuries/, 2013 (accessed on: September 5th, 2013). [8] P. V. Abbott, Diagnosis and Management of Transverse Root Fractures, Journal of Endodontic, Vol. 45, No. 12, 2019, pp. S13-S27, https://doi.org/ 10.1016/j.joen.2019.05.009. [9] M. Torabinejad, Mineral Trioxide Aggregate Properties and Clinical Applications. John Wiley & Sons, Inc, USA, 2005. [10] R. V. Roudsari, S. Jawad, C. Taylor, J. Darcey, A. Qualtrough, Modern Endodontic Principles Part 8: The Future of Endodontics, Dental Update, Vol. 43, No. 5, 2016, pp. 430-441, https://doi.org/10.12968/denu.2016.43.5.430. [11] F. Guerrero, A. Mendoza, D. Ribas, K. Aspiazu, Apexification: A Systematic Review, Journal of Conservative Dentistry, Vol. 21, No. 5, 2018, pp. 462, https://doi.org/10.4103/jcd.jcd_96_18. [12] R. Rothom , P. Chuveera, Differences in Healing of a Horizontal Root Fracture as Seen on Conventional Periapical Radiography and Cone-Beam Computed Tomography, Case Reports in Dentistry, Vol. 2017, 2017, pp. 1-5, https://doi.org/10.1155/2017/2728964. [13] N. Hadziabdic, The Basics of Splinting in Dentoalveolar Traumatology, Maxillofacial Surgery and Craniofacial Deformity - Practices and Updates, 2020, pp. 1-16, https://doi.org/10.5772/intechopen.88061. [14] S. Gautam, A. Thapa, Composite Wire Splint , an Economical , Maintainable and Flexible Option , in Stabilizing Luxated , Avulsed and Intruded Teeth : A Prospective Study, Nepal Medical College Journal, Vol. 18, No. 3-4, 2016, pp. 124-127. [15] K. Oikarinen, Comparison of the Flexibility of Various Splinting Methods for Tooth Fixation, International Journal of Oral and Maxillofacial Surgery, Vol. 17, No. 2, 1988, pp. 125-127. https://doi.org/10.1016/S0901-5027(88)80166-8. [16] K. Oikarinen, Tooth Splinting: A Review of the Literature and Consideration of the Versatility of a Wire‐Composite Splint, Dental Traumatology, Vol. 6, No. 6, 1990, pp. 237-250, https://doi.org/ 10.1111/j.1600-9657.1990.tb00426.x. [17] S. C. Kwan, J. D. Johnson, N. Cohenca, The Effect of Splint Material and Thickness on Tooth Mobility After Extraction and Replantation Using a Human Cadaveric Model, Dental Traumatology, Vol. 28, No. 4, 2012, pp. 277-281, https://doi.org/10.1111/j.16009657.2011.01086.x. [18] M. Khalid Saeed, T. Muhammad Arslan, W. Ali, S. S. Kazmi, A Comparison of Two Wire-Composite Splints Having Different Wire Diameters in the Management of Traumatic Dental Injuries, Pakistan Oral & Dental Journal, Vol. 39, No. 1, 2019, pp. 56, https://www.podj.com.pk/index.php/podj/article/view/348 (accessed on: September 5th, 2013). [19] Y. Zhu, H. Chen, L. Cen, J. Wang, Influence of Abutment Tooth Position and Adhesive Point Dimension on the Rigidity of a Dental Trauma Wire-Composite Splint, Dental Traumatology, Vol. 32, No. 3, 2016, pp. 225-230, https://doi.org/ 10.1111/edt.12241. [20] K. A. Ebeleseder, K. Glockner, C. Pertl, P. Städtler, Splints Made of Wire and Composite: an Investigation of Lateral Tooth Mobility In vivo, Dental Traumatology, Vol. 11, No. 6, 1995, pp. 288-293, https://doi.org/10.1111/j.1600-9657. 1995.tb00506.x. [21] C. Berthold, A. Thaler, A. Petschelt, Rigidity of Commonly Used Dental Trauma Splints, Dental Traumatology, Vol. 25, No. 3, 2009, pp. 248-255, https://doi.org/10.1111/j.16009657.2008.00683.x. [22] C. Berthold, F. J. Auer, S. Potapov, A. Petschelt, Influence of Wire Extension and Type on Splint Rigidity - Evaluation by a Dynamic and a Static Measuring Method, Dental Traumatology, Vol. 27, No. 6, 2011, pp. 422-431, https://doi.org/10.1111/j.16009657.2011.01033.x. [23] G. Hu, J. Y. Heithersay, Australian Dental Association, Australian Dental Journal, Vol. 56, No. 4, 2011, pp. S16-S17, https://doi.org/10.1111/ j.1834-7819.1974.tb05045.x. [24] B. Kahler, J. Y. Hu, C. S. M. Smith, G. S. Heithersay, Splinting of Teeth Following Trauma: A Review and a New Splinting Recommendation, Australian Dental Journal, Vol. 61, 2016, pp. 59-73, https://doi.org/10.1111/adj.12398. [25] H. S. Zagalska, K. Emerich, Assessment of a Power Chain as a New Dental Trauma Splint and Its Comparison With Two Commonly Used Splinting Materials, Applied Sciences, Vol. 10, No. 23, 2020, pp. 1-13, https://doi.org/10.3390/app10238398. [26] M. W. B. Hassan, L. Andersson, P. W. Lucas, Stiffness Characteristics of Splints for Fixation of Traumatized Teeth, Dental Traumatology, Vol. 32, No. 2, 2016, pp. 140-145, https://doi.org/10.1111/edt.12234. [27] T. Shirako, H. Churei, T. Wada, M. Uo, T. Ueno, Establishment of Experimental Models to Evaluate the Effectiveness of Dental Trauma Splints, Dental Materials Journal, Vol. 36, No. 6, 2017, pp. 731-739, https://doi.org/10.4012/dmj.2016-333. [28] J. O. Andreasen, F. M. Andreasen, A. Skeie, E. H. Hansen, O. Schwartz, Effect of Treatment Delay upon Pulp and Periodontal Healing of Traumatic Dental Injuries - A Review Article, Dental Traumatology, Vol. 18, No. 3, 2002, pp. 116-128, https://doi.org/10.1034/j.1600-9657.2002.00079.x. [29] J. O. Andreasen, F. M. Andreasen, I. Mejàre, M. Cvek, Healing of 400 Intra-Alveolar Root Fractures. 2. Effect of Treatment Factors such as Treatment Delay, Repositioning, Splinting Type and Period and Antibiotics, Dental Traumatology, Vol. 20, No. 4, 2004, pp. 203-211, https://doi.org/10.1111/j.1600-9657.2004.00278.x. [30] R. R. Welbury, M. J. Kinirons, P. Day, K. Humphreys, T. A. Gregg, Outcomes for Root-Fractured Permanent Incisors: A Retrospective Study, Pediatric Dentistry, Vol. 24, No. 2, 2002, pp. 98-102. [31] L. Shafie, F. Farzaneh, M. A. Hashemipour, Repair of Horizontal Root Fracture: A Case Report, Iranian Endodontic Journal, Vol. 6, No. 4, 2011, pp. 176-178, https://doi.org/10.22037/iej.v6i4.2464 [32] A. Majorana, S. Pasini, E. Bardellini, E. Keller, Clinical and Epidemiological Study of Traumatic Root Fractures, Dental Traumatology, Vol. 18, No. 2, 2002, pp. 77-80, https://doi.org/10.1034/j.16009657.2002.180206.x. [33] F. M. Andreasen, J. O. Andreasen, T. Bayer, Prognosis of Root‐Fractured Permanent Incisors — Prediction of Healing Modalities, Dental Traumatology, Vol. 5, No. 1, 1989, pp. 11-22, https://doi.org/10.1111/j.1600-9657.1989.tb00331.x. [34] Y. J. A. Kim, N. P. Chandler, Determination of Working Length for Teeth With Wide or Immature Apices: A Review, International Endodontic Journal, Vol. 46, No. 6, 2013, pp. 483-491, https://doi.org/10.1111/iej.12032. [35] F. Goldberg, S. Frajlich, S. Kuttler, E. Manzur, B. B. Marroquín, The Evaluation of Four Electronic Apex Locators in Teeth with Simulated Horizontal Oblique Root Fractures, Journal of Endodontics, Vol. 34, No. 12, 2008, pp. 1497-1499, https://doi.org/10.1016/j.joen.2008.09.002. [36] J. O. Andreasen, B. Farik, E. C. Munksgaard, Long-Term Calcium Hydroxide as a Root Canal Dressing may Increase Risk of Root Fracture, Dental Traumatology, Vol. 18, No. 3, 2002, pp. 134-137, https://doi.org/10.1034/j.1600-9657 .2002.00097.x. [37] D. R. Prithviraj, H. K. Bhalla, R. Vashisht, K. M. Regish, P. Suresh, An Overview of Management of Root Fractures, Kathmandu University Medical Journal, Vol. 12, No. 47, 2014, pp. 217-225, https://doi.org/10.3126/ kumj.v12i3.13724. [38] M. Singh, M. M. Khan, B. L. Bhavya, H. Tiwari, P. Gupta, A. Choudhary, Success Rate of Calcium Hydroxide vs Mineral Trioxide Aggregate as Apexification Agents : A Systematic Review, Annals of the Romanian Society for Cell Biology, Vol. 25, No. 6, 2021, pp. 835-839, https://www.annalsofrscb.ro/index.php/journal/article/view/5499 (accessed on: September 5th, 2013). [39] C. M. Bramante, R. Menezes, I. G. Moraes, N. Bernardinelli, R. B. Garcia, A. Letra, Use of MTA and Intracanal Post Reinforcement in a Horizontally Fractured Tooth: A Case Report, Dental Traumatology, Vol. 22, No. 5, 2006, pp. 275-278, https://doi.org/10.1111/j.1600-9657.2006.00353.x. [40] G. Erdem, A. P. Ozdas, D. O. Dincol, E. Aren, Case Series-Root Healing with MTA after Horizontal Fracture, European Archives of Paediatric Dentistry: Official Journal of the European Academy of Paediatric Dentistry, Vol. 10, No. 2, 2009, pp. 110-113, https://doi.org/10.1007/BF03321611. [41] K. Er, D. Çelik, T. Taşdemir, T. Yildirim, Treatment of Horizontal Root Fractures Using a Triple Antibiotic Paste and Mineral Trioxide Aggregate: A Case Report, Oral Surgery, Oral Medicine, Oral Pathology, Oral Radiology, and. Endodontology, Vol. 108, No. 1, 2009, pp. 63-66, https://doi.org/ 10.1016/j.tripleo.2009.03.028. [42] A. Kusgoz, T. Yildirim, M. Tanriver, C. Yesilyurt, Treatment of Horizontal Root Fractures Using MTA as Apical Plug: Report of 3 Cases, Oral Surgery, Oral Medicine, Oral Pathology, Oral Radiology, and Endodontology, Vol. 107, No. 5, 2009, pp. e68-e72, https://doi.org/10.1016/j.tripleo.2009.01.031. [43] D. Kim, W. Yue, T. C. Yoon, S. H. Park, E. Kim, Healing of Horizontal Intra-Alveolar Root Fractures after Endodontic Treatment with Mineral Trioxide Aggregate, Journal of Endodontics, Vol. 42, No. 2, 2016, pp. 230-235, https://doi.org/10.1016/j.joen.2015.11.016. [44] P. Yadav, P. J. Pruthi, R. R. Naval, S. Talwar, M. Verma, Novel Use of Platelet-Rich Fibrin Matrix and MTA as an Apical Barrier in the Management of a Failed Revascularization Case, Dental Traumatology, Vol. 31, No. 4, 2015, pp. 328-331, https://doi.org/10.1111/edt.12168.